2023
DOI: 10.1039/d3tc00740e
|View full text |Cite
|
Sign up to set email alerts
|

Versatile robust organogels based on a low molecular weight gelator of phenylquinolinylacrylonitrile

Abstract: Herein, we have synthesized three new phenylquinolinylacrylonitrile derivatives. It is found that ((Z)-2-phenyl-3-(quinolin-4-yl)acrylonitrile) (1) and ((Z)-2-(4-fluorophenyl)-3-(quinolin-4-yl)acrylonitrile) (2) can form organogels in polar solvents, and compound 2 shows good gelation ability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…It is well known that α-cyanostilbenes exhibit good self-assembling ability and aggregation-induced emission behaviors, 37 and have potential applications in chemosensors, organic light-emitting diodes (OLED) or biological imaging devices. 38 Besides, α-cyanostilbenes can undergo photoisomerization, 37 [2+2] cycloaddition 39 and electrocyclic reactions 40 in the solid states. Li et al reported that the position of the CN group in α-cyanostilbenes has a great influence on the electronic structures, intermolecular interactions, packing modes and photophysical properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that α-cyanostilbenes exhibit good self-assembling ability and aggregation-induced emission behaviors, 37 and have potential applications in chemosensors, organic light-emitting diodes (OLED) or biological imaging devices. 38 Besides, α-cyanostilbenes can undergo photoisomerization, 37 [2+2] cycloaddition 39 and electrocyclic reactions 40 in the solid states. Li et al reported that the position of the CN group in α-cyanostilbenes has a great influence on the electronic structures, intermolecular interactions, packing modes and photophysical properties.…”
Section: Introductionmentioning
confidence: 99%
“…24–42 Organogels detecting volatile acids through changes in aggregation induced emission in gel and in film are less often reported in the literature. 43–66…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular gels formed by low-molecular-weight gelators have recently attracted considerable attention because of their numerous practical applications, such as photovoltaics, field-effect transistors, oil or dye absorption, , drug release, , medical treatment, , and various sensors for gases, cation, anion, neutral molecules, and light . These supramolecular gels are composed of a large number of solvents and a small amount of gelator.…”
Section: Introductionmentioning
confidence: 99%